Dinamika Konsep Diri pada Remaja Perempuan Pembaca Teenlit - Novia Dwi Rahmaningsih; Wisjnu Martani (Jurnal Psikologi, 2014)
This study aimed to understand the dynamics of self-concept among teenage girls who read teenlit. The subjects of this study were three high school students who had actively read teenlit for at least two years. In addition, the data were obtained also from five informants who often interacted and could provide an overview about the subjects. This study used a qualitative method with phenomenological approach. Data were collected through in-depth interview on subjects and informants, observation during interview and use of teenlit as written document. The findings indicated that characters in teenlit influenced the girls’ self-concept through the mechanism of social comparison and modeling. By observing various characters found in the teenlits they read, they tended to pay attention to a teenlit’s characters that are superior to themselves. Therefore, such comparison led them to have negative self-concept. However, if they had made critical self-appraisal based on a motive of self-improvement while comparing themselves with the characters, they would have had positive self-concept. It can be concluded that a character that is considered better may become a model for the formation of an ideal self-concept. Through modeling, youth also form an actual self-concept of which is previously less aware. Keywords: modeling, self-concept, social comparison, teenlit